Proposed symptom-based model of the origins of schizophrenia. (January 2020) - Cook, John R.; Platek, Steven M.; Espinoza, Carlos N.
Abstract: Schizophrenia is considered a severe mental illness and effects an estimated 1% of the world population. The evidence suggests that incidence rate has been and will continue to be stable over time. Here we adopt a symptomatology-focused evolutionary informed approach to discuss the possible biological adaptations of various presentations of schizophrenia. It is our contention that rather than thinking about schizophrenia as a single disorder, or even a spectrum of disorders, marked by social maladaptation and personal subjective distress, that an evolutionary interpretation based on adaptive nature of individual, or small clusters of, symptoms could prove to be more useful in better understanding the pathophysiology of schizophrenia and its relationship with other psychiatric diagnoses.